Ebony gate - Vee, Julia; Bebelle, Ken (Vee, Julia. Phoenix hoard, 2023)
"Julia Vee and Ken Bebelle's Ebony Gate is a female John Wick story with dragon magic set in contemporary San Francisco's Chinatown. Emiko Soong belongs to one of the eight premier magical families of the world. But Emiko never needed any magic. Because she is the Blade of the Soong Clan. Or was. Until she's drenched in blood in the middle of a market in China, surrounded by bodies and the scent of blood and human waste as a lethal perfume. The Butcher of Beijing now lives a quiet life in San Francisco, importing antiques. But when a shinigami, a god of death itself, calls in a family blood debt, Emiko must recover the Ebony Gate that holds back the hungry ghosts of the Yomi underworld. Or forfeit her soul as the anchor. What's a retired assassin to do but save the City By The Bay from an army of the dead?"--